Session-to-session variations of internal load during different small-sided games: a study in professional soccer players - Younesi, S.; Rabbani, A.; Clemente, F. M.; Sarmento, H.; Figueiredo, A. (Research in Sports Medicine, 2021)
The aim of this study was to analyse variations of internal load across small-sided games (SSG) in professional soccer. Twenty players (mean ± SD; age 28.1±4.6 yo, height 176.7±4.9 cm, weight 72.0±7.8 kg) performed 3v3, 4v4, and 6v6 formats with/without goalkeeper and touch limitations. Each condition was repeated over three sessions and heart rate (HR) measures including average HR (HRavg), Edwards` training impulse (Edwards` TRIMP) and time in red zone (>80% of maximal HR) were recorded. All measures had trivial-to-moderate typical error (TE) and trivial differences were observed within intervals. The HRavg showed less coefficient of variations (0.9% to 1.7%) compared to Edwards`TRIMP.min-1 and red zone.min-1 (2% to 9.7%). A reduction trend in TE was observed when touching limitations or using goalkeepers. Practitioners can use different SSG formats but if the aim is to have less noise at higher intensities, more controlled drills are recommended.